Programa de habilidades comunicativas para la mejora de la comprensión lectora en estudiantes de segundo grado de educación secundaria de la institución educativa N° 60532 Leoncio Prado Río Marañón, Nauta 2024 - Sangama Sandi, Yessi (2025)
The main objective of this study was to evaluate the impact of the Communicative Skills Program on the development of reading comprehension of students in the 2nd grade of secondary school in an educational institution in Nauta. This is a quantitative research with a quasi-experimental approach and descriptive design. The population consisted of 55 students in the 2nd grade of secondary school and the sample used was 28 of the total population. The technique of direct observation and reading comprehension test was applied and questionnaires were used as instruments. The results show that the students in the experimental group (EG) obtained a significant increase of 7.96 points on the 20-point scale of the Ministry of Education (MINEDU), from the pre-test to the post-test. In contrast, the students of the control group only increased 1.77 points, which indicates a significant difference in favor of the EG. The most relevant conclusion was the following: The implementation of the Communicative Skills Program produced a notable effect on reading comprehension, which was confirmed by the application of the Student's t test, thus validating the hypothesis put forward.